The determinants of inflation volatility: a panel data analysis for US-product categories. - Arespa-Castelló, Marta; González-Alegre, Juan (Taylor & Francis Group, 2022)
Some macroeconomic dimensions like the economic business cycle, the exchange rate move- ments when the degree of country openness is significant, or the level of inflation are often considered to explain measured-inflation dynamics. However, inflation volatility may also be affected by statistical agencies methodological changes. This paper explores both potential explanations in a panel data for 100 United States CPI-U subcategories. Using both unconditional and conditional variances, we find that crucial changes in how agencies consider quality adjust- ment in products, together with the macroeconomic variables help to understand CPI volatility over time, both in the short-run and in the long-run.
Keywords: Precios; Macroeconomía; Inflación; CPI inflation volatility; GARCH; EWMA; Volatility persistence; Quality adjustment; Panel data